TITIK KRITIS PENERAPAN HALAL SUPPLY CHAIN PADA KOMODITAS DAGING SAPI DI PASAR TRADISIONAL WONOKROMO SURABAYA - Rahmadana, Rayhan Fahreza; Basya, Maziyah Mazza (Investama : Jurnal Ekonomi dan Bisnis, 2025)
This research aims to identify and analyze the critical points of implementing a halal supply chain for beef commodities in the Wonokromo Traditional Market, Surabaya. The method used is qualitative research with primary data collection through interviews and field observations, as well as secondary data from relevant documents. The research results show that the beef supply chain includes four main critical points, namely the slaughtering process, handling of materials, storage, and transportation. The slaughtering process is carried out at the Kedurus slaughterhouse, which is halal-certified, supervised by halal supervisors, and adheres to Islamic procedures. The handling of materials by meat traders is based on two purchasing approaches: whole cow purchases and item-by-item purchases, with the main challenge being the cleanliness of tools and work areas. The majority of meat storage is done using freezers to maintain quality, although the cleanliness of the freezers is an important aspect that must be considered. In transportation, traders use pick-up trucks without special packaging to maintain air circulation, but this increases the risk of contamination from the environment. Additionally, the environment where the meat is sold, which is close to chicken coops, presents additional challenges related to cleanliness and contamination risks. This research emphasizes that the application of halal principles at every stage of the supply chain is crucial for maintaining the halal status and quality of beef products. The results of this research are expected to serve as a guide for traditional market players in improving halal supply chain management and providing protection to both Muslim and non-Muslim consumers.